ROLE OF SPORTS IN NATIONAL DEVELOPMENT OF INDIA - Agarwal, Mukesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sports is ushering in a new era in India. New enthusiasm, motivation, and better state of the art safe infrastructure have made the experts more dedicated and demonstrative. Another reason for including sports is that various sports provide the youth with an opportunity for social interaction, allowing them to develop the knowledge, skills and attitudes necessary for their full participation in civil society. Both culture and sports are considered to be the basic rights of human beings. Sports are an integral part of our lives, since ancient times, sports make us practice discipline and consistency, as well as provide proper entertainment. It increases our concentration level and fills our mind with positivity. Indian people have started taking keen interest in sports and are working hard to bring medals and honour to the country. Rural people are also getting opportunities and recognizing the importance of sports, they are performing excellently.